Hold Music - Max Blansjaar (Journal of Extreme Anthropology)
The notion of sonic intimacy has received increasing scholarly attention in recent years, but less well-established has been what it means for a sonic encounter to be non-intimate. This essay proposes an opposite to sonic intimacy, namely sonic estrangement, and argues that hold music—music played to callers when they have been placed ‘on hold’—effects sonic estrangement in three ways. First, through its timbral quality, which in its lack of fullness and the fragility of signal creates a sense of distance and disjuncture. Second, through its function, which is to address the caller as an anonymous consumer, thus setting up a depersonalised relationship between caller and receiver. Third, in the way it shuts out the caller from their desired point of contact, thus symbolising an excess of demand, exclusion, and a lack of care. These three forms of estrangement counteract sonic intimacy—and can therefore be considered oppositional to it—in that they undermine three components of intimate sonic encounters: the proximate, the personal, and the attentive.